Detecção de Chlamydophila felis e Herpesvirus felino tipo 1 em felídeo não doméstico no Brasil - Seki, Meire Christina [UNESP] (2016)
Little is known about the occurrence of feline upper respiratory tract disease agents, namely Feline Herpesvirus type 1 (FHV-1) and Chlamydophila felis, and co-infection of these agents with Feline Immunodeficiency virus (FIV) and Feline Leukemia Virus (FeLV) in non-domestic felids in Brazil. Between 2009 and 2010, 72 conjunctival swab and serum samples were collected from eight non-domestic felid species [Leopardus pardalis, Leopardus tigrinus, Panthera leo, Panthera tigris, Puma concolor, Puma yagouaroundi, Oncifelis colocolo, and Panthera onca) maintained in captivity in Brazilian zoos. DNA extracted from conjunctival swabs were used in PCR assays for the detection of Chlamydophila sp, FHV-1, and retrovirus DNA, respectively. Antibodies to FIV and FeLV antigen were detected in non-domestic felid serum samples using a commercial ELISA kit. Antibodies to FIV were found only in five (6.9%) felids. No sampled non-domestic felid was positive for FeLV antigen detection. One (1.3%) out of 72 non-domestic felid conjunctival swab samples was positive for Chlamydophila_sp. and Feline Herpesvirus-1 in PCR. This felid was an ocelot and was negative for FIV and FeLV. The results of this survey showed the occurrence of co-infection with C. felis and FHV-1 in an ocelot (Leopardus pardalis) in Brazil.